Modification Of The Cylinder Head Of Performance Motorcycle - Susilo J (Bandar Lampung University (UBL), 2017)
Lately, other than as a means of transportation, motorcycles are also used for the competition performance. Methods breathing cylinder head into a simple matter to change the volume of the combustion chamber in order to increase the compression ratio. The method used is the method of experiments conducted in the laboratory. Where use 110cc Honda Beat motorcycle and premium fuels and pertalite, as well as the use of standard and modified cylinder head to determine the impact on its performance. Research carried out by using a dynamometer (dynotest) to determine the maximum power and maximum torque on a motorcycle. The results showed that the cylinder head testing using standard with premium fuel produces maximum power of 4.67 HP at rotation of 6500 rpm and maximum torque of 4.70 ft.lbs round of 4500 rpm, while the power gained 5.24 pertalite HP round 6750 rpm and a torque of 5.19 ft.lbs at 4700 rpm rotation. And testing using a modifiedcylinder head with premium fuel maximum power obtainable by 5.32 HP and a maximum torque of 4.40 ft.lbs, while pertalite obtained power of 6.34 HP and a torque of 5.17 ft.lbs